Digital Resurrection: Ai’s Role In Revitalizing Endangered Languages And The Question Of Linguistic Data Sovereignty - Shaumiwaty Shaumiwaty; Faisal Razak; Khalid Al-Naimi (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid advancement of artificial intelligence (AI) has opened new possibilities for the revitalization of endangered languages, offering tools for documentation, translation, and intergenerational transmission. However, these technological interventions raise ethical and epistemological concerns about linguistic data sovereignty the right of communities to control how their languages are represented, stored, and utilized in digital systems. Purpose. The study investigates how AI-driven language technologies contribute to both the preservation and commodification of endangered languages, examining the tension between technological innovation and cultural autonomy. The objective is to critically analyze the dual role of AI as a facilitator of linguistic resilience and as a potential vector of digital colonialism. Method. A qualitative mixed-method approach was employed, combining digital ethnography, policy analysis, and interviews with linguists, AI developers, and indigenous language activists. Data were gathered from five AI-based revitalization projects across Oceania, Africa, and North America, focusing on the implementation of machine learning models for speech recognition, corpus generation, and automated translation. Results. The findings reveal that while AI enables large-scale linguistic preservation through automation and accessibility, it also risks undermining community ownership by centralizing control of linguistic datasets within corporate or academic infrastructures. Projects that integrate community-led design and ethical data governance demonstrate higher sustainability and cultural authenticity. Conclusion. The study concludes that digital resurrection of endangered languages requires a framework grounded in data justice and participatory co-creation. AI must function not as an external savior but as a collaborative epistemic ally that empowers linguistic communities to reclaim agency in defining their digital futures.